2013
DOI: 10.1177/1471301213494509
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of quality of life among people with mild dementia in nursing home and home care—a preliminary report

Abstract: Older adults with dementia who were living at home experienced higher QoL, ADLs, and social connectedness compared with those living in institutional care. Support should be provided enabling home care and empowering caregivers to provide better care for people with dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
72
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 38 publications
6
72
0
2
Order By: Relevance
“…Elderly people with 24 dementia living in their own home tended to report higher QoL than those living in care institutions. This is supported by four studies (Kuo et al, 2010;Nikmat et al, 2015;Salvador et al, 2000;Winzelberg et al, 2005). Besides, recognised that elderly people with dementia in residential care/assisted living settings showed higher QoL than those in nursing homes.…”
Section: Religious Environmental and Other Factorssupporting
confidence: 66%
See 4 more Smart Citations
“…Elderly people with 24 dementia living in their own home tended to report higher QoL than those living in care institutions. This is supported by four studies (Kuo et al, 2010;Nikmat et al, 2015;Salvador et al, 2000;Winzelberg et al, 2005). Besides, recognised that elderly people with dementia in residential care/assisted living settings showed higher QoL than those in nursing homes.…”
Section: Religious Environmental and Other Factorssupporting
confidence: 66%
“…Most care institutions provide various facilities and professional care for elderly people with dementia, which is usually regarded as benefit for them; however, studies comparing QoL between elderly people with dementia in the community and those living in care institutions showed that living in the community contributed to a better QoL of elderly people with dementia (Nikmat et al, 2015;Kuo et al, 2010;Winzelberg et al, 2005). In addition, Borowiak & Kostka (2004) pointed out that determinants of QoL in older adults are different between in the communities and care institutions.…”
Section: Dementia and Quality Of Life (Qol)mentioning
confidence: 99%
See 3 more Smart Citations